Electron scattering and related spectroscopies - De Crescenzi, M. (Maurizio); Piancastelli, M. N. (M. Novella) (Singapore ; River Edge, NJ : World Scientific, 1996)
The book provides an overview of all phenomena which can be categorized under the general label of "electron scattering", and to give a comprehensive description of all spectroscopical techniques related to electron scattering phenomena. Various classes of events are examined (electron in-electron out, photon in-electron out, electron in-two electron out, electron diffraction), together with the corresponding experimental techniques.
A description of the underlying physics of various electron scattering phenomena is provided. For each spectroscopy the general principles, the main fields of application, and some selected representative cases are discussed. The use of relatively low-cost electron sources is emphasized with respect to photon sources. This title is directed to PhD students and researchers not necessarily yet expert in the field.
1. Introduction -- 2. Elastic Scattering Techniques: Leed and Rheed -- 3. Photoelectron and Auger Diffraction -- 4. Electron Energy Loss Spectroscopy -- 5. (e,2e) Spectroscopy -- 6. Extended Energy Loss Fine Structure -- 7. Other Electron Scattering Techniques.
Includes bibliographical references.
Keywords: Electron spectroscopy; Electrons -- Scattering; Photoelectron spectroscopy; Auger effect; Electron energy loss spectroscopy